HOW INTERNATIONAL HUMAN RESOURCE MANAGEMENT CONDUCTED BY APPLE INC. INCREASES ECONOMIC GROWTH AND REDUCE UNEMPLOYMENT RATE IN CHINA - muhammad hafiz anwar; muhammad hanif machfudz; nadhif muhammad farhan; yehezkiel triputra; ida bagus putu aditya (LIAISON JOURNAL OF BEST, 2022)
As China operates their business activities, many multinational companies contribute to helping its economic growth and reducing its unemployment rate. One of the crucial factors that contribute to the success of these companies in operating in China is its extraordinary management of the Human Resources team. With Apple Inc being a USA based company, they’re still able to adapt and compete in China. Key words: China, multinational companies, economic growth, unemployment rate, human resources, Apple Inc & USA.